CT and MRI features of extraocular muscle granular cell tumour: preliminary experience in eight cases. Issue 4 (April 2022) - Qi, M.; Zhang, F.; Pan, Y.; Chen, Y.; Ren, J.; Sha, Y.
Abstract : AIM: To characterise the computed tomography (CT) and magnetic resonance imaging (MRI) features, in particular the functional MRI characteristics, of extraocular muscle granular cell tumours (GCTs). MATERIALS AND METHODS: The CT ( n= 6) and MRI ( n= 8) features of eight extraocular muscle GCTs cofirmed at histopathology were analysed retrospectively. The imaging findings were evaluated with emphasis on the location, size, margin, shape, extent, bony change, internal architecture, enhancement pattern, and extent of lesions. Based on diffusion-weighted imaging (DWI) and dynamic contrast-enhanced (DCE) MRI, the apparent diffusion coefficient (ADC) value of six lesions and time–intensity curve (TIC) of one lesion were reviewed. RESULTS: Immunohistochemistry revealed strong positivity for S-100 protein and a low Ki-67 index (2–5%) in all cases. Most of the lesions (7/8) were confined to the muscle belly with an ovoid shape. All of the tumours were isodense to cerebral grey matter and showed homogeneously mild enhancement on CT images. All lesions were hypointense to cerebral grey matter on T2-weighted imaging (T2WI) and showed homogeneously marked enhancement on contrast-enhanced T1-weighted imaging (T1WI). All lesions showed a hypo- or isointense signal on DWI images with a high b-value. The mean ADC of six lesions was (0.72 ± 0.14) × 10 −3 mm 2 /s. The TIC of the case examined using DCE-MRI showed a plateau pattern (type II). CONCLUSION: A well-defined oval mass confined to the muscle belly with a hypointense signal on T2WI, homogeneously marked enhancement on contrast-enhanced T1WI, hypo- or isointense signal on DWI, and low ADC value is highly suggestive of a GCT. Highlights: Extraocular muscle GCT is an extremely rare neoplasm. The imaging features of it have not been fully characterized. It is mainly confined to the muscle belly with a well-defined margin. It often presents homogeneous hypointensity on T2WI with marked enhancement. Hypo- or isointense signal on DWI with a low ADC value is suggestive of it.